Survival driving : staying alive on the world's most dangerous roads - Deatherage, Robert H. (Robert Henry), Jr., 1961- (Boca Raton : CRC Press, 2022)
"Survival Driving: Staying Alive on the World's Most Dangerous Roads, Second Edition was written to inform and protect: to keep people alive by making them more situationally aware. Any person is a potential target, either from a criminal or a terrorist threat, depending on your profession and the type of environment you live and work in. Driving is the most important part of a person's security program, whether the person is traveling alone or the executive being moved by his or her security detail. The book is written in plain, easy to understand language providing straight-forward guidance that outlines tools to ensure security whenever in transit in a vehicle. This includes making themselves a hard target in order to avoid attack. While most terrorist or criminal attacks are difficult to predict, the majority of attacks take place when a person is in transit. By providing tools such as rout analysis, identifying choke points, learning where safe havens are located along a route, individuals are able to predict the places that are most vulnerable, and take steps to ensure safety. VIPs, executives, those working in-or traveling to-volatile regions of the world, and those hired to protect such individuals will equally learn how to detect surveillance when it is targeted against them, when they are the potential target. Failing this, the book also provides the tools a person needs to break contact and escape when an attack against them while moving in their vehicle occurs. The book covers basic and advanced driving skills and instructs on how to best understand the transport vehicle and its capabilities. Key Features: Instructs readers on how to recognize and anticipate potential attack sites during movement Illustrates how to properly maintain a vehicle at peak performance in different environments so it will work as required when needed Describes vehicle dynamics and, specifically, how a vehicle can be used as a tool to protect, and aid escape, when under attack Outlines the ways individuals can become more situationally aware in their movements Maps out key security driving elements such as steering, braking, vehicle dynamics, and evasive maneuvers to escape amidst a threat By raising situational awareness, increasing knowledge of the attack cycle, and outlining the nature of threats, Survival Driving can transform any reader from a soft target to an informed hard target who threat actors will want to avoid"--
OCLC-licensed vendor bibliographic record.
Keywords: Automobile driving -- Security measures; Motorcades -- Security measures; Terrorism -- Prevention; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; SOCIAL SCIENCE / Violence in Society; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement